2016
DOI: 10.1007/s00449-016-1721-7
|View full text |Cite
|
Sign up to set email alerts
|

Trans-glycosylation capacity of a highly glycosylated multi-specific β-glucosidase from Fusarium solani

Abstract: An extracellular β-glucosidase from Fusaruim solani cultivated on wheat bran was purified by only two chromatographic steps. The purified enzyme exhibited optimal temperature and pH at 60 °C and pH 5, respectively. The purified β-glucosidase behaves as a very large protein due to its high degree of glycosylation. More interestingly, the endoglycosidase H (Endo H) treatment led to 97.55% loss of its initial activity after 24 h of treatment. Besides, the addition of Tunicamycin (nucleoside antibiotic blocking th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…In the present study, Exg-D synthesised methyl-, ethyl-and propyl-cellobiosides. Several other GH enzymes have also been reported to act as trans-glycosylases, for example β-glucosidase, and cellobiose phosphorylase can produce alkyl glucosides [5,21,[23][24][25]. To the best of our knowledge, this is the first study demonstrating that GH5_38 exo-glucanases (Exg-D) can perform transglycosylation.…”
Section: Discussionmentioning
confidence: 89%
“…In the present study, Exg-D synthesised methyl-, ethyl-and propyl-cellobiosides. Several other GH enzymes have also been reported to act as trans-glycosylases, for example β-glucosidase, and cellobiose phosphorylase can produce alkyl glucosides [5,21,[23][24][25]. To the best of our knowledge, this is the first study demonstrating that GH5_38 exo-glucanases (Exg-D) can perform transglycosylation.…”
Section: Discussionmentioning
confidence: 89%
“…It was shown that there was a greater variety of hydrolases found in DEW than in CEW, suggesting certain unique functions for waterfowl. 25 It was reported that the N-linked glycans were required for the enzyme activity of β-glucosidase, 27 which was related to the carbohydrate metabolic process. Therefore, the glycans of DEW glycosidases might play an important role in stabilizing their enzymatic activities to release sugars for meeting the need for energetic fuel during embryo development.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A larger number of metabolic process related glycoproteins were found in DEW (36%) than in CEW (8%). It was reported that the enzymatic efficiency could be modulated by the glycoprotein N-glycans, 27 and the alteration of enzymatic efficiency might be related to the higher energy demand for duck.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Until the performance of the current procedures, no report was conducted about alkyl glycoside synthesis above 50 • C. Transglycosylation products were both formed by a β-glucosidase from Trichoderma harzianum and a β-glucosidase from Hanseniaspora thailandica BC9 under 30 • C [51,52]. β-Glucosidase efficiently synthesizes cellotriose and cellotetraose at 40 • C [53], however, in our work, the most thermostable mutant Bgl1D187 (S28T/Y37H/D44E/R91G/L115N) retained transglycosidation activity at 50 • C (Table 4). Some single mutations (D44G and W122G) were deleterious.…”
Section: Discussionmentioning
confidence: 99%